A conceptual model to improve building commissioning in construction projects: Case studies of a public institution of higher learning in Malaysia / Kho Mei Ye - Kho, Mei Ye (2013)
Commissioning is a systematic process of ensuring all building facility systems perform interactively in accordance with the design documentation and intent. Commissioning begins with planning and includes design, construction, start-up, acceptance and training, and should be applied throughout the life span of the building. Commissioning is usually misunderstood as a process performed after the completion of construction. Nevertheless, in the Malaysian construction industry, there are many different perceptions on building commissioning. This discrepancy on the interpretation of building commissioning by consultants and contractors as compared with the available definitions of building commissioning has led to misunderstanding of building commissioning concept in the Malaysia context. This problem is further aggravated when contractors and consultants presume that unattended problems in the beginning of a project can be mended in the commissioning phase. As such, questions will arise on whether this interference of unattended problems at the beginning of a project life-cycle will affect the planned commissioning and the timely delivery of the project. Building commissioning is the key to quality assurance in more than one way as it prevents problems from developing, anticipates and regulates system interactions, and implements a systematic method of meeting the buildings mechanical, electrical, and control requirements. However, detail research on project commissioning is relatively small in comparison to other research areas of project management such as project planning, control, success measurement, and risk assessment. This study aims to explore the current scenario of building commissioning in the Malaysian construction industry. To achieve this research aim, the objectives of this study are defined as: 1) to redefine the scope and understanding of building commissioning from the contractors’ and consultants’ perspective; 2) to identify problems during commissioning and the relationships of these problems with other phases of the project life-cycle; 3) to determine the underlying causes of identified commissioning problems; 4) to measure the importance of building commissioning and its effect on project completion by using Earned Value Analysis; and 5) to develop a conceptual model to improve building commissioning for construction projects in the public institution of higher learning in Malaysia. Case studies from a public institution of iii higher learning in Malaysia were selected, as the current process of building commissioning for buildings construction on campus for public institutions of higher learning is generally inefficient. The conceptual model aims to provide a better understanding on building commissioning for the Malaysia context and by eliminating this unattended problem, the planned duration for commissioning will not be affected and indirectly will aid the improvement of building performance. This study also intends to generate a guideline for the construction practitioners on the common activities of building commissioning that needs to be planned even during the construction stage.